Hubungan Tingkat Stres Dan Dukungan Sosial Pada Ibu Terhadap Pemberian Asi Eksklusif di Samarinda - Wisnuwardani, Ratih Wirapuspita; Afiah, Nurul; A’isyah, Siti; Noviasty, Reny; Agustini, Rina Tri (Jurnal Biomedika dan Kesehatan, 2024)
Background The COVID-19 pandemic is causing stress in all aspects of life, including nursing mothers. This situation may affect exclusive breastfeeding coverage, which was only 66% in 2020. Factors contributing to low breastfeeding rates include maternal stress and social support. The aim of this study was to determine the association between maternal stress levels and social support for exclusive breastfeeding during the COVID-19 pandemic in Wonorejo Health Center, East Kalimantan. Methods The study design was cross-sectional with a sample of 165 mothers with children aged 6-24 months. Data collection was conducted online via a questionnaire on a Google Form link provided to subjects through their WhatsApp contacts. Data were analyzed using the chi-square test and the Kolmogorov-Smirnov test. Results 55.8% of mothers had high levels of social support supporting exclusive breastfeeding, and 81.2% of mothers experienced moderate stress. Data analysis using the chi-square test and Kolmogorov-Smirnov test showed no relationship between social support (p=0.056) and stress level (p=0.969) during exclusive breastfeeding. Conclusions There was no significant association between stress levels and social support among mothers of exclusively breastfed children aged 6 to 24 months during the COVID-19 pandemic at the Wonorejo Health Center in Samarinda, East Kalimantan. Wonorejo Health Center is encouraged to continuously improve its breastfeeding promotion programs for mothers and families.